2005
DOI: 10.1182/blood-2004-04-1416
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepcidin is down-regulated in TfR2 mutant mice manifesting a phenotype of hereditary hemochromatosis

Abstract: Transferrin receptor 2 (TfR2) is a membrane glycoprotein that mediates cellular iron uptake from holotransferrin. Homozygous mutations of this gene cause one form of hereditary hemochromatosis in humans. We recently reported that homozygous TfR2(Y245X) mutant mice, which correspond to the TfR2(Y250X) mutation in humans, showed a phenotype similar to hereditary hemochromatosis. In this study, we further analyzed the phenotype as well as iron-related gene expression in these mice by comparing the TfR2-mutant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
142
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(155 citation statements)
references
References 40 publications
7
142
0
6
Order By: Relevance
“…Because TfR2 is expressed in hepatocytes, it is positioned to regulate the expression of hepcidin, a small peptide hormone synthesized and secreted by hepatocytes that controls systemic iron levels by modulating cellular iron efflux (Nicolas et al, 2001(Nicolas et al, , 2002Pigeon et al, 2001;Roetto et al, 2003;Nemeth et al, 2004). Consistent with this hypothesis, individuals and mice with disease-causing mutations in TfR2 fail to regulate hepcidin appropriately (Kawabata et al, 2005;Nemeth et al, 2005). TfR2 might, therefore, sense systemic iron levels through interaction with its ligand.…”
Section: Discussionmentioning
confidence: 52%
“…Because TfR2 is expressed in hepatocytes, it is positioned to regulate the expression of hepcidin, a small peptide hormone synthesized and secreted by hepatocytes that controls systemic iron levels by modulating cellular iron efflux (Nicolas et al, 2001(Nicolas et al, , 2002Pigeon et al, 2001;Roetto et al, 2003;Nemeth et al, 2004). Consistent with this hypothesis, individuals and mice with disease-causing mutations in TfR2 fail to regulate hepcidin appropriately (Kawabata et al, 2005;Nemeth et al, 2005). TfR2 might, therefore, sense systemic iron levels through interaction with its ligand.…”
Section: Discussionmentioning
confidence: 52%
“…It appears that the hepatocytes are the primary site for TfR2 expression and activity, because hepatocyte-specific deletion of TfR2 in mice leads to a similar iron overload phenotype as global deletion (17,18,25,28,33,35). TfR2 is also involved in the regulation of hepcidin (18,25,33), and it is likely that TfR2 activity is modulated by an interaction with transferrin. Two studies have shown that the TfR2 protein is stabilized by diferric transferrin (17,28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that a liver-specific deletion of the mouse TfR2 gene is sufficient to induce iron overload in mice (35). These and other studies have shown that liver-expressed TfR2 is important for maintaining iron homeostasis, through its regulation of the iron-regulatory hormone hepcidin (6,18,33,35). At a cellular level, however, it is still not clear how TfR2 is involved in the regulation of iron metabolism.…”
mentioning
confidence: 86%
“…Mutant forms of these proteins are responsible for different types of hemochromatosis, the most prevalent genetic disorder characterized by the deregulation of iron absorption (for review, see Fleming and Sly 36 and Pietrangelo 37 ). Interestingly, a lack of an appropriate hepcidin response to iron loading was demonstrated for the three types of hemochromatosis (HFE1, 19,20,38,39 TfR2, 40,41 and HFE2 42 ), suggesting that hepcidin is the common pathogenic denominator in iron overload syndromes. The role of these proteins in mediating hepcidin response to inflammation is less clear.…”
Section: Discussionmentioning
confidence: 99%